The role of intra-regional trade in the Pacific Alliance's integration into AsiaPacific (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
One of the objectives of the Pacific Alliance is trade integration orientated towards Asia-Pacific; However, the integration of the bloc’s members into that region’s markets is circumscribed by their low levels of intra-regional trade and their limited export diversification. On this basis, this research seeks to explain the extent to which the intra-regional trade of the Pacific Alliance affects its inclusion in the Asia-Pacific markets. The methodology research is explanatory. Indicators ofeconomic interdependence are analyzed to observe the degree of intra-regional trade within the alliance and in other Asia-Pacific regions, as well the technological content of each member’s export basket. The results show that while the Pacific Alliance’s trade has an extra-regional bias and its exports are tending towards reprimarization, this has not been an impediment to the objective of inclusion in international markets with an orientation towards Asia-Pacific as the bloc’s trade bias towards that region has increased.